Highly transparent and robust superhydrophobic coatings fabricated via a facile sol-gel process - Ke, Chong; Zhang, Chenhua; Wu, Xinguo; Jiang, Yongdong (Thin solid films, 2021)
•A highly transparent and robust superhydrophobic coating is prepared.•The optimum coating has a water contact angle (WCA) of 154°.•The superhydrophobic coating shows better transparency compared to reported studies.•The coated sample has a transmittance of 91.6% and a haze of 2.41%.•After the water droplet impact test, the WCA of the coating remains above 150°. A simple sol-gel method was utilized to fabricate SiO2-based coatings on glass substrates. After decorating the coatings with fluorosilane, the coatings became superhydrophobic, with a maximum water contact angle of 154°. After a systematic investigation of the coating processing parameters, the transparency and hydrophobicity of the coatings were well balanced. A highly transparent superhydrophobic coating was fabricated. The coated sample has an optical transmittance that is only <1% lower than the bare substrate. The coating also demonstrates high durability as evaluated by the water droplet impact test. After the test, the water contact angle of the coating was reduced by 2°. Moreover, the coating is oleophobic as well, with an oleic acid contact angle of 130°.